2007
DOI: 10.1203/pdr.0b013e3181256492
|View full text |Cite
|
Sign up to set email alerts
|

Stigmasterol, a Soy Lipid–Derived Phytosterol, Is an Antagonist of the Bile Acid Nuclear Receptor FXR

Abstract: Phytosterols, components of soy-derived lipids, are among the proposed exacerbants of parenteral nutrition-associated cholestasis (PNAC). We investigated whether phytosterols contribute to bile acid (BA)-induced hepatocyte damage by antagonizing a nuclear receptor (NR) critically involved in hepatoprotection from cholestasis, FXR (farnesoid X receptor, NR1H4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
190
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(199 citation statements)
references
References 40 publications
(34 reference statements)
3
190
1
2
Order By: Relevance
“…Although TPN is lifesaving in providing nutrition to extremely low-birth weight infants and infants with serious gastrointestinal surgical conditions, it has serious side effects, with PNALD being the foremost among them (3,8). Until recently, infants with PNALD lacked effective modes of treatment, but the recent emergence of FOLE has shown a significant reduction in the mortality and morbidity associated with established PNALD (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TPN is lifesaving in providing nutrition to extremely low-birth weight infants and infants with serious gastrointestinal surgical conditions, it has serious side effects, with PNALD being the foremost among them (3,8). Until recently, infants with PNALD lacked effective modes of treatment, but the recent emergence of FOLE has shown a significant reduction in the mortality and morbidity associated with established PNALD (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence accumulated over the past few decades strongly suggests the lipid component of TPN as the most probable cause of PNALD. Both animal and human research during the past decade has implicated phytosterols and v-6 (n-6) fatty acids as the most likely components in the current lipid formulations as primary reasons for PNALD (8)(9)(10)(11)(12). In contrast, fish oil-based lipid emulsions (FOLEs) have been shown to be associated with full resolution of PNALD (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher ratios of serum phytosterols (stigmasterol, sitosterol, and avenasterol) were found associated with direct bilirubin in infants with IFALD, compared with those without IFALD [9]. The factors associated with IFALD in patients receiving high intakes of n-6 polyunsaturated fatty acids (n-6 PUFA) with soybean oil-based IVLE are the formation of n-6 arachidonic acid, a proinflammatory mediator, the high provision of phytosterols, and the limited supply of alpha tocopherol relative to PUFA supply [1,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigating the role of different phytosterols (sitosterol, campesterol, and stigmasterol) in the induction of liver damage has shown that stigmasterol is a potent antagonist of the nuclear farnesoid X receptor FXR and the ligand-activated pregnane X receptor (a member also of the NR superfamily involved in the bile acid metabolism and inflammation), while sitosterol and campesterol had minimal or insignificant inhibitory effects in a human-derived liver cell line HepG2 (15). In addition to the agonist action of the liver X receptors (LXRs) (highly expressed in the liver, adipose tissue, intestine, kidney, and macrophages with involvement in sterol transport, fatty acid metabolism, glucose regulation, immunity , and cellular response), stigmasterol also interferes with the processing of sterol response element binding protein-2 (SREBP-2), which is a central regulatory factor in cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 99%